A new species of Spinicauda (Nematoda: Heterakidae) from Gonocephalus kuhlii (Reptilia: Agamidae) of Ciremai Mountain, Java-Indonesia - Dewi, Kartika; Purwaningsih, Endang; Riyanto, Awal; Bursey, Charles R. (Zootaxa, 2021)
Spinicauda ciremaiensis sp. nov. (Nematoda: Heterakidae) from the large intestine of Gonocephalus kuhlii (Reptilia: Agamidae) collected in Gunung Ciremai National Park, West Java, Indonesia is described and illustrated. Of the five described species of Spinicauda from the Oriental region, Spinicauda ciremaiensis sp. nov. comes closest to S. sumatrana in having 14 pairs of caudal papillae and the presence of a tail filament. However, the new species differs from S. sumatrana in the longer spicula, smaller eggs, and weak sclerotization of the gubernaculum. S. ciremaiensis sp. nov. is also the only species belonging to the genus Spinicauda which has a sclerotized accessories piece of gubernaculum. A key to the species of Spinicauda is also provided. [http://zoobank.org/urn:lsid:zoobank.org:act:785F2D63-E5EB-4E4C-A7E1-7F7E7AD7C392]